The pleiotropic transcriptional regulator NlpR contributes to the modulation of nitrogen metabolism, lipogenesis and triacylglycerol accumulation in oleaginous rhodococci - Hernández, Martín Alejandro (2017)
The regulatory mechanisms involved in lipogenesis and triacylglycerol (TAG) accumulation are largely unknown in oleaginous rhodococci. In this study a regulatory protein (here called NlpR: Nitrogen lipid Regulator), which contributes to the modulation of nitrogen metabolism, lipogenesis and triacylglycerol accumulation in oleaginous rhodococci was identified. Under nitrogen deprivation conditions, in which TAG accumulation is stimulated, the nlpR gene was significantly upregulated, whereas a significant decrease of its expression and TAG accumulation occurred when cerulenin was added. The nlpR disruption negatively affected the nitrate/nitrite reduction as well as lipid biosynthesis under nitrogen-limiting conditions. In contrast, its overexpression increased TAG production during cultivation of cells in nitrogen-rich media. A putative ‘NlpR-binding motif’ upstream of several genes related to nitrogen and lipid metabolisms was found. The nlpR disruption in RHA1 strain led to a reduced transcription of genes involved in nitrate/nitrite assimilation, as well as in fatty acid and TAG biosynthesis. Purified NlpR was able to bind to narK, nirD, fasI, plsC and atf3 promoter regions. It was suggested that NlpR acts as a pleiotropic transcriptional regulator by activating of nitrate/nitrite assimilation genes and others genes involved in fatty acid and TAG biosynthesis, in response to nitrogen deprivation.